476. SONIC HEDGEHOG POSITIVE EXPRESSION IS ASSOCIATED WITH PROGNOSIS AND THE RESPONSE OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA TO NEOADJUVANT CHEMOTHERAPY. (24th September 2022) - Sun, Haibo; Liu, Xianben; Xing, Wenqun; Feng, Shaokang; Jiang, Duo; Yan, Sen; Ma, Yaxing
Abstract: Neoadjuvant therapy follow by surgery is the standard treatment mode for patients with locally advanced esophageal squamous cell carcinoma (ESCC). This research aimed to investigated the potential of sonic hedgehog (Shh), glioma-associated oncogene homolog1 (Gli1) and Phospho-S6 (p-S6) to predict the response of ESCC to neoadjuvant chemotherapy. Firstly, the expressions of Shh, Gli1 and p-S6 in cancer tissues and normal tissues of 49 ESCC patients without neoadjuvant therapy were detected by immunohistochemistry. A total of 390 ESCC patients were included in the nest study, and 44 pairs of patients with or without neoadjuvant chemotherapy were matched after 1:1 propensity score matching to evaluate the effect of neoadjuvant chemotherapy on the expression of Shh, Gli1 and p-S6. The relationship between Shh, Gli1, and p-S6 expression and the outcomes of neoadjuvant chemotherapy was analyzed retrospectively. The expressions of Shh (positive/negative: 25/24 vs. 0/49, P﹤0.001), Gli1 (24/25 vs. 0/49, P﹤0.001) and p-S6 (16/33 vs. 0/49, P﹤0.001) in cancer tissues were significantly higher than those in normal tissues. Neoadjuvant chemotherapy did not change the expression of Shh (24/20 vs. 23/21, P=0.109), Gli1 (23/21 vs. 21/23, P=0.839) and p-S6 (10/34 vs. 15/29, P=0.383) in ESCC cancer tissues. Among them, the positive expression of Shh was associated with poor tumor regression grade (TRG2-3/TRG1: 23/1 vs. 12/8, P=0.003) and poor 5-year survival rate (44.7% vs. 65.8%, P=0.041). The expressions of Shh, Gli1 and p-S6 were increased significantly in ESCC and were not affected by neoadjuvant chemotherapy. Shh is a significant predictive indicator of ESCC response to neoadjuvant chemotherapy and prognosis.